In-vitro release study of cassia alata-loaded PLGA microspheres - Alfatama, Mulham; Ahmad, Kausar; Mohamed, Farahidah (2011)

(untitled)
Senna Alata or Cassia Alata (C. Alata) is a plant belonging to the family Leguminosae and has been documented to have antifungal and antimicrobial activities. The purpose of this study was to design poly-(lactide-co-glycolide) (PLGA) microspheres for a controlled delivery of the C. Alata extract, over 2–4 weeks. The microspheres were produced by solvent evaporation technique and the desired characteristics, i.e. high encapsulation efficiency and controlled release over 2–4 weeks had been achieved by several optimised parameters including oil/aqueous ratio and the use of buffer system. In vitro drug release of these microspheres was performed in a phosphate-buffered saline solution (pH 7.4) for certain period of time. A prolonged in vitro drug release profile was observed. The release profiles of C. Alata from PLGA microspheres were found to occur with an initial burst release followed by a gradual release phase up to one month. Drug release rates were dependent upon the types of the surfactants employed during the microspheres preparation. It was found that high initial burst release occurred with all types of surfactant used, however higher initial burst was noticed with hydrophilic surfactant (3% Tween 20) at 58.49%. In conclusion, the optimization of formulation parameters allowed us to produce C. Alata loaded PLGA microspheres of suitable characteristics for therapeutic use.